Solvent-Free Synthesis of Ultrafine Tungsten Carbide Nanoparticles-Decorated Carbon Nanosheets for Microwave Absorption - Lian, Yunlong; Han, Binhua; Liu, Dawei; Wang, Yahui; Zhao, Honghong; Xu, Ping; Han, Xijiang; Du, Yunchen (Nano-Micro Letters, 2020)
Carbides/carbon composites are emerging as a new kind of binary dielectric systems with good microwave absorption performance. Herein, we obtain a series of tungsten carbide/carbon composites through a simple solvent-free strategy, where the solid mixture of dicyandiamide (DCA) and ammonium metatungstate (AM) is employed as the precursor. Ultrafine cubic WC1−x nanoparticles (3–4 nm) are in situ generated and uniformly dispersed on carbon nanosheets. This configuration overcomes some disadvantages of conventional carbides/carbon composites and is greatly helpful for electromagnetic dissipation. It is found that the weight ratio of DCA to AM can regulate chemical composition of these composites, while less impact on the average size of WC1−x nanoparticles. With the increase in carbon nanosheets, the relative complex permittivity and dielectric loss ability are constantly enhanced through conductive loss and polarization relaxation. The different dielectric properties endow these composites with distinguishable attenuation ability and impedance matching. When DCA/AM weight ratio is 6.0, the optimized composite can produce good microwave absorption performance, whose strongest reflection loss intensity reaches up to − 55.6 dB at 17.5 GHz and qualified absorption bandwidth covers 3.6–18.0 GHz by manipulating the thickness from 1.0 to 5.0 mm. Such a performance is superior to many conventional carbides/carbon composites. Highlights: 1 Ultrafine tungsten carbide nanoparticles-decorated carbon nanosheets were successfully fabricated via a simple solvent-free strategy. 2 The chemical composition of tungsten carbide/carbon composites can be easily manipulated by the weight ratio of dicyandiamide to ammonium metatungstate. 3 The advantages in good performance and simple preparation provide a promising prospect for the application of these tungsten carbide/carbon composites.